Mitigating Ventilator-Induced Lung Injury: The Role of Tidal Volume and Pressure Control in Thoracic Surgery Patients undergoing decortication - Jawad Hameed, Muhammad Imran (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Ventilator-induced lung injury (VILI) is one of the most common Thoracic surgery complications, and especially in cases of pleural decortication. The decision over the ventilator method can be a cure to relieve this injury. Objective: To evaluate the impact of tidal volume and pressure control strategies on the incidence and severity of ventilator-induced lung injury in thoracic surgery patients undergoing pleural decortication. Materials and Method: This was a prospective observational study at the Lady Reading Hospital MTI Peshawar, Pakistan from November, 2022 to April, 2023. Sixty patients were randomized to the two groups. PCV and VCV are terms that indicate the pressure-controlled ventilation and the volume-controlled ventilation. The intraoperative factors and the postoperative complications were documented and compared in both groups. Results: The PCV group demonstrated an increased level of oxygenation while the peak pressures and VILI were reduced. Also, the ICU stay and extended tube ventilation were shortened in the patients included in the PCV group. Conclusion: PCV provides a better lung protection and thoracic decortication patients’ recovery than VCV. Keywords: Ventilator-induced lung injury, pressure-controlled ventilation, volume-controlled ventilation, thoracic decortication, one-lung ventilation, postoperative complications.